Noninvasive Cerebral Perfusion and Oxygenation Monitoring Augment Prolonged Field Care in a Non-Human Primate Model of Decompensated Hemorrhage and Resuscitation. Issue 3 (March 2021) - Morgan, Clifford G.; Neidert, Leslie E.; Stigall, Kyle S.; Rodriguez, Gerardo J.; Pratt, Gilbert A.; Lonowski, Dominic; Harrell, Kelly; McNeal, Neal D.; Tiller, Michael M.; Cardin, Sylvain; Glaser, Jacob J.
ABSTRACT: Background: Decompensated hemorrhagic shock (DHS) is the leading cause of preventable death in combat casualties. "Golden hour" resuscitation effects on cerebral blood flow and perfusion following DHS in prolonged field care (PFC) are not well investigated. Using an established non-human primate model of DHS, we hypothesized noninvasive regional tissue oxygenation (rSO2 ) and Transcranial Doppler (TCD) would correlate to the invasive measurement of partial pressure of oxygen (PtO2 ) and mean arterial pressure (MAP) in guiding hypotensive resuscitation in a PFC setting. Methods: Ten rhesus macaques underwent DHS followed by a 2 h PFC phase (T0–T120), and subsequent 4 h hospital resuscitation phase (T120–T360). Invasive monitoring (PtO2, MAP) was compared against noninvasive monitoring systems (rSO2, TCD). Results were analyzed using t tests and one-way repeated measures ANOVA. Linear correlation was determined via Pearson r. Significance = P  < 0.05. Results: MAP, PtO2, rSO2, and mean flow velocity (MFV) significantly decreased from baseline at T0. MAP and PtO2 were restored to baseline by T15, while rSO2 was delayed through T30. At T120, MFV returned to baseline, while the Pulsatility Index significantly elevated by T120 (1.50 ± 0.31). PtO2 versus rSO2 (R 2  = 0.2099) and MAP versus MFV (R 2  = 0.2891) shared very weak effect sizes, MAP versus rSO2 (R 2  = 0.4636) displayed a low effect size, and PtO2 versus MFV displayed a moderate effect size (R 2  = 0.5540). Conclusions: Though noninvasive monitoring methods assessed here did not correlate strongly enough against invasive methods to warrant a surrogate in the field, they do effectively augment and direct resuscitation, while potentially serving as a substitute in the absence of invasive capabilities.